Witchery as Tribal Primary Ethos: Negotiations and Resistance in Select Literary Representations - Saru Sachdeva; Rekha Rani (IAFOR Journal of Arts & Humanities)
The belief in the existence of both benevolent and malevolent spirits among tribal communities in India has led to the emergence of numerous narratives surrounding witchcraft. Central to these beliefs is the notion of a spiritual realm that sustains the witch cult, where witches are typically portrayed as women. Deeply embedded in religious practices, traditions, folklore, and myths, the concept of witchcraft serves to reinforce gendered power dynamics within tribal societies. This, in turn, contributes to the heightened vulnerability of tribal women within the broader, non-tribal social structure. The present study seeks to explore the concept of witchcraft as it is understood, experienced, and deconstructed by tribal women themselves, as represented in the Indian fictional works The Mysterious Ailment of Rupi Baskey by Hansda Sowvendra Shekhar and The Witch by Mahasweta Devi. Employing a deconstructive approach, this paper critically examines witchcraft as a core aspect of tribal cultural identity. It argues that Indian tribal women no longer view witchcraft merely as a negative gender stereotype but rather as a means to assert their rights, celebrate their autonomy, and navigate the complexities of a mystical belief system. By resisting the oppressive use of witchcraft as a tool of manipulation, tribal women, through their strategic engagement with witchcraft, challenge both tribal and non-tribal systems of oppression, thereby forging their own identities and redefining the boundaries of power.